Implementation of management support tools projects in IT companies - Albiniak, Radosław; Miłosz, Elżbieta (Journal of Computer Sciences Institute, 2019)
The article presents the evaluation of tools to support IT project management. The research was carried out using the diagnostic survey method on the assessment of the implementation of tools to support IT project management.